The Importance of Developmental Centers in Preparing Preschool Children for School (Eurasian Journal of Learning and Academic Teaching, 2023)
In the article, the further improvement of the preschool education system, the study of advanced foreign experiences in the field of preschool education organization, innovative methods and effective pedagogical practices in the field of education and upbringing of preschool children, development in quality preparation of children for school education the importance of centers and the essence of the organization of development centers are discussed.